A World Trade Leading Index (WTLI) - Barhoumi, Karim (IMF Working Papers; Working Paper, 2015)
This paper develops a new monthly World Trade Leading Indicator (WTLI) that relies on nonparametric and parametric approaches. Compared to the CPB World Trade Monitor's benchmark indicator for global trade the WTLI captures turning points in global trade with an average lead between 2 and 3 months. We also show that this cyclical indicator is able to track the annual growth rate in global trade, suggesting that the recent slowdown is due in part to certain cyclical factors. This new tool can provide policy makers with valuable foresight into the future direction of economic activity by tracking world trade more efficiently.